Electrochemical device and electronic device including the same

By using a nanofiber porous matrix separator filled with low-melting-point polymer particles in lithium-ion batteries, the problems of current blocking and mechanical strength during thermal runaway are solved, thereby improving the safety and self-discharge performance of the battery.

CN115428249BActive Publication Date: 2024-12-31NINGDE AMPEREX TECHNOLOGY LTD
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
CN202080095652.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-03-27
Publication Date
2024-12-31
Estimated Expiration
2040-03-27

AI Technical Summary

Technical Problem

The existing membrane-free lithium-ion battery's separator layer cannot block current under thermal runaway conditions, posing a safety hazard. Furthermore, it has low mechanical strength and severe self-discharge.

Method used

A nanofiber porous matrix isolation layer containing low-melting-point polymer particles is used. The low-melting-point polymer particles melt and seal the pores during thermal runaway, blocking the current and improving mechanical strength.

Benefits of technology

It improves battery safety performance, reduces self-discharge, and enhances the mechanical strength of the separator to prevent short circuits caused by penetration of the positive and negative electrode active materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115428249B_ABST
    Figure CN115428249B_ABST
Patent Text Reader

Abstract

An electrochemical device and an electronic device comprising the electrochemical device. The electrochemical device comprises an electrode plate and an isolation layer (10) on at least one surface of the electrode plate, wherein the isolation layer (10) comprises a nanofiber porous matrix (101) and polymer particles (102) distributed in the nanofiber porous matrix (101), and the melting temperature of the polymer particles (102) is 70°C to 150°C. Compared with the prior art, since the isolation layer (10) has low-melting-point polymer particles (102) distributed in the nanofiber porous matrix (101), the isolation layer (10) has a low-temperature thermal pore-closing function, and can cut off the current under thermal runaway to improve the safety performance of the electrochemical device. The low-melting-point polymer particles (102) are filled in the "macropores" of the fiber porous matrix to reduce the macropores, thereby further improving the self-discharge problem of the electrochemical device and reducing the K value, while reducing the internal short circuit problem of the positive and negative active material particles in the electrochemical device piercing the isolation layer (10), which is also conducive to improving the electrical performance of the electrochemical device such as the cycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemistry, and more specifically, to an electrochemical device and an electronic device comprising the electrochemical device. Background Art

[0002] Lithium-ion batteries have many advantages such as high energy density, long cycle life, high nominal voltage (>3.7V), and low self-discharge rate, and are widely used in the field of consumer electronics. With the rapid development of electric vehicles and mobile electronic devices in recent years, people have higher and higher demands on battery energy density (>700Wh / L), safety, cycle performance (>500 cycles), etc., and are looking forward to the emergence of new lithium-ion batteries with comprehensive performance improvements. Among them, diaphragm-free lithium-ion batteries are a new type of lithium-ion battery that has attracted much attention.

[0003] The diaphragm-free lithium-ion battery adopts the method of preparing the isolation layer on the surface of the electrode plate to replace the traditional isolation membrane. The diaphragm-free lithium-ion battery integrates the isolation layer directly into the surface of the electrode plate, and there is no need to make the isolation membrane separately. The production process changes from the three components of the electrode plate-isolation membrane-pole plate to the stacking / winding of the two components of (integrated) pole plate-(integrated) pole plate, which simplifies the battery production process and reduces the difficulty of battery preparation; at the same time, the thinning of the isolation layer thickness increases the battery energy density; in addition, the diaphragm-free battery technology also has many advantages such as increasing the porosity of the isolation layer to improve the liquid retention capacity and accelerate the reaction kinetics, so it has received widespread attention.

[0004] Existing membrane-free lithium-ion batteries usually use non-woven isolation layers. The non-woven isolation layer is formed by directional or random bonding of nano or micro fibers. The random overlap between the fibers forms a large number of pores for ion transmission, and the fibers themselves serve as the supporting skeleton of the isolation layer. However, this fiber layer does not have the function of thermal closure. In the case of thermal runaway (such as battery overcharge, hot box, vibration, collision, fall, internal short circuit, external short circuit, etc.), it cannot block the current by melting and shutting off the lithium ion path, which poses a great hidden danger to the safety performance of lithium-ion batteries; secondly, the mechanical strength of the fiber layer of the non-woven isolation layer itself is low, resulting in the positive and negative electrode particles penetrating the fiber layer when resisting the puncture of the positive and negative electrode particles, causing a short circuit in the electrochemical device; in addition, the pore size of the fibers of the non-woven isolation layer is large and unevenly distributed. The presence of some "large pores" will cause lithium-ion batteries to have serious self-discharge problems. Summary of the invention

[0005] Based on the defects of the prior art, the first aspect of the present application first provides an electrochemical device, which includes an electrode plate and an isolation layer on at least one surface of the electrode plate, wherein the isolation layer comprises a porous matrix of nanofibers and polymer particles distributed in the porous matrix, and the melting temperature of the polymer particles is 70°C to 150°C.

[0006] In some preferred embodiments of the first aspect of the present application, the number of the polymer particles in the isolation layer is 1×10 8 / m 2 Up to 1×10 18 / m 2 .

[0007] In some preferred embodiments of the first aspect of the present application, the average particle size of the polymer particles is 40 nm to 10 μm.

[0008] In some preferred embodiments of the first aspect of the present application, the diameter of the nanofiber is 10 nm to 5 μm, and the pore size of the fibrous porous matrix is ​​40 nm to 10 μm.

[0009] In some preferred embodiments of the first aspect of the present application, some polymer particles extend from the surface of the porous matrix to a height of 0.1 nm to 5 μm, and the surface area of ​​the porous matrix surface occupied by the some polymer particles is 0.1% to 60% of the total surface area of ​​the porous matrix.

[0010] In some preferred embodiments of the first aspect of the present application, the polymer of the polymer particles includes at least one of polystyrene, polyethylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, acrylonitrile-butadiene-styrene, polylactic acid, polyvinyl chloride, polyvinyl butyral or polyacrylate.

[0011] In some preferred embodiments of the first aspect of the present application, the nanofibers contain a polymer, and the polymer includes at least one of polyvinylidene fluoride, polyimide, polyamide, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polyphenylene ether, polypropylene carbonate, polymethyl methacrylate, polyethylene terephthalate, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-co-chlorotrifluoroethylene) and their derivatives, preferably at least one of polyvinylidene fluoride, polyimide, polyamide, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polyphenylene ether, polypropylene carbonate, polymethyl methacrylate, polyethylene terephthalate and their derivatives.

[0012] In some preferred embodiments of the first aspect of the present application, a ratio β / α between the cross-sectional void ratio β of the isolation layer and the surface open porosity α of the isolation layer is less than 95%.

[0013] In some preferred embodiments of the first aspect of the present application, the surface open porosity α is 35% to 90%.

[0014] In some preferred embodiments of the first aspect of the present application, the cross-sectional void fraction β is 30% to 85%.

[0015] In a second aspect of the present application, an electronic device is provided, which comprises the electrochemical device described in any one of the above technical solutions.

[0016] The electronic devices described in the present application include electronic devices known in the art, such as laptop computers, mobile phones, electric motorcycles, electric cars, electric toys, etc.

[0017] Compared with the prior art, since the isolation layer of the present application has low-melting-point polymer particles distributed in the nanofiber porous matrix, the isolation layer has a low-temperature thermal closed-cell function, which can cut off the current under thermal runaway to improve the safety performance of the electrochemical device; in addition, the low-melting-point polymer particles can be filled in the "macroporous" of the fiber porous matrix to reduce the macropores in the simple heat-resistant spinning isolation layer, thereby further improving the self-discharge problem of the electrochemical device and reducing the K value. At the same time, due to the improvement of the mechanical strength of the isolation layer, the internal short-circuit problem of the positive and negative active material particles inside the electrochemical device piercing the isolation layer is reduced, which is also beneficial to improving the electrochemical performance of the electrochemical device such as cycling. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present application and the technical solutions of the prior art, the following briefly introduces the drawings required for use in the embodiments and the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 A schematic diagram of the structure of an electrode assembly according to an embodiment of the present application;

[0020] Figure 2 A schematic diagram of the structure of an electrode assembly according to an embodiment of the present application;

[0021] Figure 3 A schematic diagram of the structure of an electrode assembly according to an embodiment of the present application;

[0022] Figure 4 A schematic diagram of the structure of an electrode assembly according to an embodiment of the present application;

[0023] Figure 5 A schematic diagram of the structure of an isolation layer in one embodiment of the present application;

[0024] Figure 6 A schematic diagram of the structure of an isolation layer in one embodiment of the present application;

[0025] Figure 7A schematic diagram of an embodiment of preparing an isolation layer of the present application;

[0026] Figure 8 It is a schematic diagram of an embodiment of preparing an isolation layer of the present application.

[0027] Reference numerals:

[0028] 10: Isolation layer;

[0029] 101: nanofiber porous matrix;

[0030] 102: polymer particles;

[0031] 103: Inorganic particles;

[0032] 20: Current collector;

[0033] 201: positive electrode current collector;

[0034] 202: negative electrode current collector;

[0035] 30: active material layer;

[0036] 301: positive electrode active material layer;

[0037] 302: negative electrode active material layer;

[0038] 40: conductive layer;

[0039] 401: positive electrode conductive layer;

[0040] 402: negative electrode conductive layer;

[0041] 50: Spinning equipment;

[0042] 60: Electrodeposition equipment;

[0043] 70: Voltage stabilizer. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical scheme, and advantages of the present application more clearly understood, the present application is further described in detail with reference to the accompanying drawings and embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application.

[0045] The electrochemical device described in the present application is not particularly limited, and can be any electrochemical device that can use the present application, such as a lithium-ion battery, a supercapacitor, etc. For the convenience of description, the following description is taken as an example of a lithium-ion battery, but this does not mean that the electrochemical device of the present application is limited to a lithium-ion battery.

[0046] One aspect of the present application provides an electrochemical device, which includes an electrode plate and an isolation layer on at least one surface of the electrode plate, wherein the isolation layer comprises a nanofiber porous matrix and polymer particles distributed in the porous matrix, and the melting temperature of the polymer particles is 70°C to 150°C, preferably 80°C to 140°C, more preferably 90°C to 130°C, and most preferably 100°C to 120°C.

[0047] In some embodiments of the present application, the porous matrix is ​​formed by nanofibers being oriented or randomly combined together, and the random overlap between the nanofibers forms a large number of pores for ion transmission, while the nanofibers themselves serve as the supporting skeleton of the isolation layer, and the polymer particles are filled in the porous matrix. Due to the low melting temperature of the polymer particles, when the electrochemical device has thermal runaway, for example, when the battery is overcharged, hot box, vibration, collision, fall, internal short circuit, external short circuit, etc., the temperature of the electrochemical device rises, and after reaching the melting point of the polymer particles, the polymer particles melt, close the pores of the isolation layer, reduce or block the conduction of lithium ions, and reduce or stop the charge and discharge of the electrochemical device, which can greatly improve the safety of the electrochemical device. In addition, the nanofiber porous matrix itself has a high melting temperature. In the case of thermal abuse such as overcharge / hot box, the isolation layer maintains the original structure without shrinking and causing membrane breakage, avoiding the occurrence of internal short circuit. In addition, since the polymer particles are distributed in the pores of the porous matrix and fill the macropores in the porous matrix, the self-discharge phenomenon can be effectively reduced. In addition, since the polymer particles are distributed in the porous matrix, the puncture resistance of the porous matrix is ​​improved, which can effectively prevent the positive and negative active material particles from piercing the isolation layer and causing a short circuit in the electrochemical device. In addition, the nanofiber porous matrix has good adhesion to the pole piece, which can effectively prevent the diaphragm from being washed by the electrolyte and folded during the fall of the electrochemical device, greatly improving the safety performance of the electrochemical device.

[0048] The number of polymer particles in the isolation layer is not particularly limited, as long as the purpose of the present application can be achieved. In some embodiments of the present application, the number of polymer particles in the isolation layer is 1×10 8 / m 2 Up to 1×10 18 / m 2 , preferably 1×10 9 / m 2 Up to 1×10 16 / m 2 , more preferably 1×10 10 / m 2 Up to 1×10 14 / m 2 , the most preferred is 1×10 11 / m 2 Up to 1×1013 / m 2 By limiting the number of polymer particles within the above range, when thermal runaway occurs in the electrochemical device, it can respond quickly, shorten the time from melting to closed pores, block the ion path, and improve the safety performance of the electrochemical device. In addition, the puncture resistance of the isolation layer can be better improved, preventing the positive and negative active material particles from piercing the isolation layer, and effectively reducing the macropores in the porous matrix, reducing the self-discharge phenomenon, and reducing the K value.

[0049] There is no particular limitation on the particle size of the polymer particles, as long as the purpose of the present application can be achieved. In some embodiments of the present application, the average particle size of the polymer particles is 40nm to 10μm, preferably 100nm to 5μm, more preferably 200nm to 2μm, and most preferably 500nm to 1.5μm. When the average particle size of the polymer particles is within the above range, the macropores in the porous matrix can be better reduced or eliminated, and the self-discharge phenomenon can be reduced. In addition, when the average particle size of the polymer particles is within the above range, the pores in the isolation layer can be fully and quickly closed in the case of thermal runaway of the electrochemical device, the ion conduction path can be blocked, an insulating layer can be formed, and the battery can be prevented from catching fire and exploding.

[0050] The diameter of the nano or micron fiber is not particularly limited, as long as the purpose of the present application can be achieved. In some embodiments of the present application, the diameter of the nanofiber is 10nm to 5μm, preferably 20nm to 2μm, more preferably 50nm to 1μm, and most preferably 80nm to 400nm. By making the diameter of the nanofiber within the above range, the isolation layer can have a suitable porosity, improve the liquid retention capacity of the isolation layer, and ensure that the porous matrix has a suitable strength, and cooperate with the polymer particles distributed in the porous matrix to improve the mechanical strength of the isolation layer, and enhance the ability of the isolation layer to resist puncture of positive and negative active material particles. In the isolation layer, the pore size of the porous matrix is ​​not particularly limited, as long as the purpose of the present application can be achieved. In some preferred embodiments of the present application, the pore size of the porous matrix isolation layer is 40nm to 10μm, preferably 80nm to 5μm, more preferably 130nm to 1μm, and most preferably 150nm to 500nm. Without being limited to any theory, the inventors believe that the pore size of the porous matrix isolation layer within the above range can accelerate lithium ion transmission and improve reaction kinetics. At the same time, it can effectively reduce the probability of positive and negative electrode active material particles passing through the isolation layer, reducing the risk of self-discharge and internal short circuit. In addition, during the thermal runaway process of the electrochemical device, the molten polymer particles can quickly fill the pores of the isolation layer, realize the isolation layer closed pores, block ion transmission, and improve the safety performance of the electrochemical device.

[0051] In a preferred embodiment of the present application, some polymer particles extend from the surface of the porous matrix to a height of 0.1nm to 5μm, preferably 1nm to 1μm, more preferably 2nm to 500nm, and most preferably 5nm to 100nm. Without being limited to any theory, the inventors believe that the polymer particles extend from the porous matrix to a certain height, which can reduce the force of the positive and negative electrode active material particles on the porous matrix itself, and further prevent the positive and negative electrode particles from piercing the isolation layer. The surface area of ​​the porous matrix surface occupied by the part of the polymer particles is 0.1% to 60% of the total surface area of ​​the porous matrix, preferably 0.5% to 45%, more preferably 2% to 30%, and most preferably 5% to 15%. Without being limited to any theory, the inventors believe that the surface area of ​​the porous matrix surface occupied by the polymer particles extending from the surface is within the above range, which can make the isolation layer have higher strength and the ability to resist piercing of the positive and negative electrode active material particles.

[0052] In the present application, the “porous substrate surface” refers to the surface of the isolation layer that is away from the active material layer after the isolation layer is coated on the active material layer.

[0053] The polymer type of the polymer particles used in the present application is not particularly limited as long as the melting point is 70 to 150° C. In some embodiments of the present application, the polymer particles include at least one of polystyrene (PS), polyethylene (PE), ethylene-propylene copolymer, polypropylene (PP), ethylene-vinyl acetate copolymer (EVA), acrylonitrile-butadiene-styrene (ABS), polylactic acid (PLA), polyvinyl chloride (PVC), polyvinyl butyral (PVB) or polyacrylate (PA).

[0054] The shape of the polymer particles used in the present application is not particularly limited, and can be spherical, olive-shaped, elongated, flat, pie-shaped, annular, rod-shaped, hollow, spiral, core-shell, gourd-shaped, cylindrical, cone, rectangular, cube, pyramid, prism or at least one of other arbitrary shapes.

[0055] The nanofiber used in this application is not particularly limited, as long as the purpose of this application can be achieved, any material known to those skilled in the art can be used. In some embodiments of the present application, the nanofiber comprises a polymer, and the polymer includes polyvinylidene fluoride (PVDF), polyimide (PI), polyamide (PA), polyacrylonitrile (PAN), polyethylene glycol (PEG), polyethylene oxide (PEO), polyphenylene ether (PPO), polypropylene carbonate (PPC), polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), poly (vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), poly (vinylidene fluoride-co-chlorotrifluoroethylene) (PVDF-PCTFE) and at least one of its derivatives, preferably polyvinylidene fluoride, polyimide, polyamide, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polyphenylene ether, polypropylene carbonate, polymethyl methacrylate, polyethylene terephthalate and at least one of its derivatives. Preferably, in some embodiments of the present application, the melting point of the polymer is not less than 170 ° C. When the polymer nanofibers having a melting point of not less than 170°C are used, in the case of thermal runaway, the polymer particles begin to melt at a relatively low temperature, for example, at 70 to 150°C, thereby closing the ion transport channels of the isolation layer. However, the nanofiber skeleton does not melt at this temperature, and the original structure of the isolation layer is maintained without shrinking, thereby ensuring that a short circuit in the battery will not occur due to shrinkage / rupture of the isolation layer, thereby improving the safety of the electrochemical device.

[0056] The polymer of the nanofiber may also contain inorganic particles, which are not particularly limited and can be inorganic particles known to those skilled in the art. For example, the inorganic particles may include at least one of HfO2, SrTiO3, SiO2, Al2O3, MgO, CaO, NiO, BaO, ZnO, TiO2, ZrO2, SnO2, CeO2, boehmite, magnesium hydroxide or aluminum hydroxide. The size of the inorganic particles is not particularly limited, for example, it can be 10nm to 10μm. The content of the inorganic particles is not particularly limited, for example, it can be 0.1% to 80%. By adding inorganic particles, the mechanical strength of the isolation layer can be further enhanced, the self-discharge phenomenon of the electrochemical device can be reduced, and the safety performance of the electrochemical device can be improved.

[0057] In some preferred embodiments of the present application, the surface porosity α of the isolation layer is 35% to 90%, preferably 45% to 87%, more preferably 60% to 85%, and most preferably 75% to 82%. The cross-sectional porosity β of the isolation layer is 30% to 85%, preferably 40% to 80%, more preferably 50% to 75%, and most preferably 55% to 65%. The ratio β / α between the cross-sectional porosity β of the isolation layer and the surface porosity α of the isolation layer is 95% or less, preferably 20% to 90%, more preferably 40% to 85%, and most preferably 65% ​​to 80%.

[0058] By controlling the surface open porosity and cross-sectional porosity of the isolation layer within the above ranges, the isolation layer can be provided with high liquid retention capacity, maintain appropriate strength, and have fast reaction kinetics.

[0059] The thickness of the isolation layer according to the present application is not particularly limited, and those skilled in the art can select it according to the specific situation, preferably 1 μm to 20 μm, preferably 2 μm to 18 μm, more preferably 5 μm to 15 μm, and most preferably 6 μm to 12 μm. The thickness of the isolation layer refers to the overall thickness of the integrated isolation layer including the nanofiber porous matrix and the polymer particles.

[0060] The electrochemical device of the present application may be a lithium-ion battery. The present application has no limitation on the type of lithium-ion battery, and may be any type of lithium-ion battery, such as button-type, cylindrical, soft-pack lithium-ion battery, etc.

[0061] The lithium-ion battery of the present application comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and an isolation layer as described in any one of the above items of the present application.

[0062] In one embodiment of the present application, the isolation layer can be formed on one surface of the positive electrode sheet and one surface of the negative electrode sheet, and then stacked in the manner of negative electrode sheet + isolation layer, positive electrode sheet + isolation layer to form a lithium-ion battery stack.

[0063] In another embodiment of the present application, the isolation layer can be formed on both surfaces of the positive electrode sheet, and then stacked in the manner of negative electrode sheet, isolation layer + positive electrode sheet + isolation layer to form a lithium-ion battery stack, wherein there is no isolation layer on the surface of the negative electrode sheet.

[0064] In another embodiment of the present application, the isolation layer can be formed on both surfaces of the negative electrode plate, and then stacked in the manner of positive electrode plate, isolation layer + negative electrode plate + isolation layer to form a lithium-ion battery stack, wherein there is no isolation layer on the surface of the positive electrode plate.

[0065] The stacked body formed in the above embodiment can be further stacked in the above order, or can be directly wound to form a multi-layer lithium ion battery stacked body. The present application has no limitation on the stacking method, and those skilled in the art can choose according to actual conditions.

[0066] Figure 1 The schematic diagram of the electrode assembly structure of an embodiment of the present application is shown. In which, an isolation layer is provided on one surface of the electrode plate. The isolation layer 10 covers the surface of the electrode active material layer 30, and the electrode active material layer 30 is located on one surface of the current collector 20.

[0067] Figure 2 A schematic diagram of the electrode assembly structure of an embodiment of the present application is shown, wherein the isolation layer 10 is located between the positive electrode active material layer 301 and the negative electrode active material layer 302, the positive electrode active material layer 301 is located on one surface of the positive electrode collector 201, and the negative electrode active material layer 302 is located on one surface of the negative electrode collector 202.

[0068] Figure 3 A schematic structural diagram of an electrode assembly according to an embodiment of the present application is shown, which further includes a conductive layer 40 , which is located between the electrode active material layer 30 and the current collector 20 , and the isolation layer 10 covers the surface of the electrode active material layer 30 .

[0069] Figure 4 A schematic diagram of the electrode assembly structure of an embodiment of the present application is shown, which further includes a positive conductive layer 401 and a negative conductive layer 402, wherein the positive conductive layer 401 is located between the positive current collector 201 and the positive active material layer 301, and the negative conductive layer 402 is located between the negative current collector 202 and the negative active material layer 302.

[0070] Figure 5 A schematic diagram of the isolation layer structure of an embodiment of the present application is shown, wherein polymer particles 102 are located in a nanofiber matrix 101 .

[0071] Figure 6 A schematic diagram of the isolation layer structure of an embodiment of the present application is shown, wherein polymer particles 102 and inorganic particles 103 are located in a nanofiber matrix 101 .

[0072] In the embodiments of the present application, the positive electrode plate is not particularly limited, as long as the purpose of the present application can be achieved. For example, the positive electrode plate generally comprises a positive current collector and a positive active material. Among them, the positive current collector is not particularly limited, and can be any positive current collector known in the art, such as aluminum foil, aluminum alloy foil or composite current collector. The positive active material is not particularly limited, and can be any positive active material of the prior art, and the active material includes at least one of NCM811, NCM622, NCM523, NCM111, NCA, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.

[0073] Optionally, the positive electrode plate may further include a conductive layer, the conductive layer being located between the positive electrode current collector and the positive electrode active material. The composition of the conductive layer is not particularly limited, and may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a binder.

[0074] In the embodiments of the present application, the negative electrode plate is not particularly limited, as long as the purpose of the present application can be achieved. For example, the negative electrode plate generally comprises a negative electrode current collector and a negative electrode active material. Among them, the negative electrode current collector is not particularly limited, and any negative electrode current collector known in the art can be used, such as copper foil, copper alloy foil or composite current collector. The negative electrode active material is not particularly limited, and any negative electrode active material known in the art can be used. For example, it can include at least one of graphite, hard carbon, soft carbon, silicon, silicon carbon or silicon oxide.

[0075] Optionally, the negative electrode plate may further include a conductive layer, the conductive layer being located between the negative electrode current collector and the negative electrode active material. The composition of the conductive layer is not particularly limited, and may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive agent and a binder.

[0076] The conductive agent described above is not particularly limited, and any conductive agent known in the art can be used, as long as the purpose of the present application can be achieved. For example, the conductive agent can include at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fiber or graphene. For example, the conductive agent can be conductive carbon black (Super P). The adhesive described above is not particularly limited, and any adhesive known in the art can be used, as long as the purpose of the present application can be achieved. For example, the adhesive can include at least one of styrene-butadiene rubber (SBR), polyvinyl alcohol (PVA), polytetrafluoroethylene (PTFE) or sodium carboxymethyl cellulose (CMC-Na). For example, the adhesive can be styrene-butadiene rubber (SBR).

[0077] The electrolyte of the lithium-ion battery is not particularly limited, and any electrolyte known in the art can be used, which can be any of a gel state, a solid state and a liquid state. For example, the liquid electrolyte includes a lithium salt and a non-aqueous solvent.

[0078] The lithium salt is not particularly limited, and any lithium salt known in the art can be used as long as the purpose of the present application can be achieved. For example, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3 or LiPO2F2. For example, the lithium salt may be LiPF6.

[0079] The non-aqueous solvent is not particularly limited as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include at least one of carbonate compounds, carboxylate compounds, ether compounds, nitrile compounds or other organic solvents.

[0080] For example, the carbonate compound may include at least one of diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate, etc.

[0081] The present application does not particularly limit the preparation method of the electrochemical device, and the preparation can be carried out by methods known in the art. For example, nanofibers and polymer particles are deposited on one or both surfaces of the positive electrode sheet or the negative electrode sheet to form a porous matrix containing nanofibers and polymer particles filled in the porous matrix.

[0082] Alternatively, nanofibers, polymer particles and inorganic particles are deposited on one or both surfaces of the positive electrode sheet or the negative electrode sheet to form a porous matrix containing nanofibers and polymer particles and inorganic particles filled in the porous matrix.

[0083] The method for depositing nanofibers, polymer particles and / or inorganic particles is not particularly limited, and can be carried out by a deposition method known in the art, for example, the porous matrix is ​​prepared by electrospinning, air spinning, centrifugal spinning, electroblowing, melt blowing, flash evaporation or coating, and the polymer particles and / or inorganic particles are prepared by electrodeposition, printing, coating, rotation or impregnation. The order of depositing nanofibers, polymer particles and / or inorganic particles is not particularly limited, as long as the isolation layer of the present application can be formed, and the isolation layer comprises a nanofiber porous matrix and polymer particles and / or inorganic particles distributed in the porous matrix. For example, the nanofibers and polymer particles and / or inorganic particles can be deposited simultaneously or alternately.

[0084] Figure 7 It is a schematic diagram of an electrospinning process of the present application; the electrospinning device 50 deposits nanofibers on the electrode surface to form an isolation layer 10.

[0085] Figure 8 This is a schematic diagram of an implementation scheme for preparing an isolation layer of the present application, wherein an electrospinning device 50 and an electrodeposition device 60 deposit nanofibers and polymer particles on an electrode surface, respectively; and the electrospinning device 50 and the electrodeposition device 60 are both connected to a potentiostat 70.

[0086] The porous matrix can be implemented with any spinning equipment known in the art without any particular limitation, as long as the purpose of this application can be achieved. The electrospinning method can use any electrospinning equipment known in the art, for example, the electrospinning equipment can be the Yongkang Leye Elite series, etc.; the gas spinning method can use any gas spinning equipment known in the art, for example, the gas spinning equipment can be the air-jet spinning machine of Nanjing Jienas New Materials, etc.; the centrifugal spinning method can use any centrifugal spinning equipment known in the art, for example, the centrifugal spinning equipment can be the centrifugal spinning machine of Sichuan Zhiyan Technology, etc. The electrodeposition method can be implemented with any equipment known in the art without any particular limitation, as long as the purpose of this application can be achieved. The electrospraying method can use any electrospraying equipment known in the art, for example, the electrostatic spraying equipment of Sames, France can be used.

[0087] The present application also provides an electronic device, which includes the electrochemical device according to the present application.

[0088] The electronic devices described in the present application include common electronic devices in the art, such as laptop computers, mobile phones, electric motorcycles, electric cars, electric toys, etc.

[0089] The terms used in this application are generally terms commonly used by those skilled in the art. If there is any inconsistency with commonly used terms, the terms in this application shall prevail.

[0090] Specifically, in this application, the following terms have the following meanings:

[0091] Sectional void ratio: The percentage of void area on any section perpendicular to the surface of the isolation layer to the total section area.

[0092] Surface open porosity: The percentage of the surface area of ​​open pores on the surface of the isolation layer to the total surface area.

[0093] Number of polymer particles: the total number of polymer particles per unit area of ​​the isolation layer.

[0094] Average particle size of polymer particles: The average particle size of polymer particles is expressed by D50, where D represents the diameter of the polymer particles. D50 is the particle size corresponding to 50% of the cumulative particle size distribution percentage of the polymer particles based on volume distribution. Its physical meaning is that particles with a diameter smaller than it account for 50%, and particles with a diameter larger than it also account for 50%.

[0095] Test method:

[0096] Test method for closed-cell temperature of insulation layer:

[0097] The positive electrode current collector containing single-sided active material + isolation layer + negative electrode current collector containing single-sided active material sample is infiltrated with electrolyte, wherein the active material is adjacent to the isolation layer. The multi-channel thermometer contact is placed at the isolation layer. The above combination is placed on the test fixture plate, a pressure of 10MPa is applied and an AC impedance tester is connected, and then it is placed in a 50°C oven and heated at 2°C / min. The temperature corresponding to the resistance reaching 1000Ω is recorded, which is the closed-pore temperature of the isolation layer.

[0098] Isolation layer rupture temperature test method:

[0099] Place the positive electrode current collector containing single-sided active material + isolation layer + negative electrode current collector containing single-sided active material sample on the test fixture plate, place the multi-channel thermometer contacts on the isolation layer, and then apply a pressure of 10MPa. Connect the above device to the conductivity tester, and then place it in a 50℃ oven and heat it at 2℃ / min. The temperature corresponding to the conductivity indication is the membrane rupture temperature of the isolation layer.

[0100] 1C-1.5U (U is the cut-off voltage) 1h overcharge performance test method:

[0101] Discharge the lithium-ion battery to 3.0V, then charge it to 1.5U at a constant current of 1C, and then charge it at a constant voltage for 1h. If there is no fire or explosion, it passes the test and is recorded as pass.

[0102] 150℃, 1h hot box performance test method:

[0103] Place the fully charged lithium-ion battery in an oven, heat the oven to 150°C at a heating rate of 5±2°C / min, and keep it for 1 hour before stopping. If there is no fire or explosion, it passes the test and is recorded as pass.

[0104] Test method for the porosity ε of the isolation layer:

[0105] The porosity ε of the isolation layer is determined by the weight M of the isolation layer. 隔离层 and volume V 隔离层 , the mass fraction of the porous matrix and polymer particles in the isolation layer is w 多孔基体 and w 聚合物颗粒 , and their densities ρ 多孔基体 and ρ 聚合物颗粒 Calculated, ε=(V 隔离层 -V 多孔基体 -V 聚合物颗粒 ) / V 隔离层 *100%, where V 多孔基体 =M 隔离层 *w 多孔基体 / ρ 多孔基体 , V 聚合物颗粒 =M 隔离层 *w 聚合物颗粒 / ρ 聚合物颗粒 .

[0106] Cross-sectional void ratio β test method:

[0107] Place the prepared isolation layer cross section under a scanning electron microscope equipped with a certain number of grid reference objects for observation, select a unit area, count the grids covering the gaps, and the ratio of the grid area covering the gaps to the selected area is the cross-sectional void ratio β1 of the isolation layer. Repeat this method, select unit areas at different cross sections and different positions of the isolation layer to calculate the cross-sectional void ratio, and the cross-sectional void ratios are β2, β3, β4...β n Therefore, the cross-sectional porosity β of the isolation layer is β1, β2, β3, β4...β n The mean value of β(%)=n / (β1+β2+β3+β4+……+β n ).

[0108] Surface open porosity α test method:

[0109] The measured isolation layer is placed under a scanning electron microscope equipped with a certain number of grid reference objects for observation. The unit area is selected and the number of grids covering the pores is counted. The ratio of the grid area covering the pores to the selected area is the surface porosity α1 of the isolation layer. This method is repeated, and the unit area at different positions on the isolation layer surface is selected to measure the surface porosity. The surface porosities are α2, α3, α4...α n Therefore, the surface opening rate α of the isolation layer is α1, α2, α3, α4...α n The mean value of α(%)=n / (α1+α2+α3+α4+......+α n ).

[0110] Lithium-ion battery self-discharge rate K value test method:

[0111] Discharge the lithium-ion battery at 0.5C to 3.0V and let it stand for 5 minutes. Then charge the lithium-ion battery at 0.5C constant current to 3.85V, then charge it at 3.85V constant voltage to a current of 0.05C, let it stand for two days in an environment of 25℃±3℃, test and record the voltage at this time as OCV1. Then, let the lithium-ion battery stand for another two days at room temperature, test and record the voltage at this time as OCV2, and the K value can be obtained by the following formula: K (mV / h) = (OCV2-OCV1) / 48h*1000

[0112] Discharge capacity after 50 charge and discharge cycles / first discharge capacity η test method:

[0113] The lithium-ion battery was charged to 4.4V at a constant current of 0.5C, then charged to a current of 0.05C at a constant voltage of 4.4V, left to stand at 25℃±3℃ for 10min, and then discharged to 3.0V at a current of 0.5C. The first discharge capacity was recorded as Q 1D Repeat the cycle 50 times and record the discharge capacity as Q 50D , then the discharge capacity after 50 charge and discharge cycles / the retention rate of the first discharge capacity: η(%) = Q 50D / Q 1D *100%

[0114] Example

[0115] Preparation Example 1: Preparation of negative electrode sheet

[0116] The negative electrode active material graphite, conductive carbon black (Super P), and styrene-butadiene rubber (SBR) are mixed in a weight ratio of 96:1.5:2.5, and deionized water (H2O) is added as a solvent to prepare a slurry with a solid content of 0.7, and stirred evenly. The slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 8μm, and dried at 110°C to obtain a negative electrode sheet with a coating thickness of 130μm and coated on one side with negative electrode active material. Repeat the above steps on the other surface of the negative electrode sheet to obtain a negative electrode sheet with double-sided coating of negative electrode active material. Then, the sheet is cut into a specification of 41mm×61mm for standby use.

[0117] Preparation Example 2: Preparation of positive electrode sheet

[0118] The positive electrode active material lithium cobalt oxide (LiCoO2), conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97.5:1.0:1.5, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 0.75, and stirred evenly. The slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 90°C to obtain a positive electrode sheet with a coating thickness of 110μm. On the other surface of the positive electrode current collector aluminum foil, the above steps are repeated to obtain a double-sided coated positive electrode sheet. After coating, the sheet is cut into a specification of 38mm×58mm for standby use.

[0119] Preparation Example 3: Preparation of electrolyte

[0120] In a dry argon atmosphere, organic solvents ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are first mixed in a mass ratio of EC:EMC:DEC=30:50:20, and then lithium salt lithium hexafluorophosphate (LiPF6) is added to the organic solvent to dissolve and mix evenly to obtain an electrolyte with a lithium salt concentration of 1.15M.

[0121] The following examples illustrate the preparation of the nanofiber porous matrix + polymer particle integrated isolation layer according to the present application. These embodiments are described by taking the positive electrode plate as an example, and an integrated isolation layer is deposited on both surfaces of the positive electrode plate. It should be understood that the integrated isolation layer can also be deposited on both surfaces of the negative electrode plate, or an integrated isolation layer can be deposited on one surface of the positive electrode plate and one surface of the negative electrode plate, respectively, and these embodiments can also achieve the purpose of the present application. Those skilled in the art should understand that these embodiments are also within the scope of protection of the present application.

[0122] Embodiment 1:

[0123] Polyvinylidene fluoride (PVDF) was dispersed in a dimethylformamide (DMF) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. Low melting point polyethylene (PE) particles were dispersed in an N-methylpyrrolidone (NMP) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%.

[0124] On one surface of the positive electrode plate of Preparation Example 2, solution A is used as a raw material to prepare a PVDF fiber porous matrix by an electrospinning method. While spinning, suspension B is used as a raw material to spray low-melting polyethylene (PE) particles by an electrospraying method to form an integrated isolation layer of a fiber porous matrix + a low-melting polymer with a thickness of 10 μm, and the low-melting polymer particles are distributed in the fiber porous matrix in a filling manner. Among them, the average fiber diameter is 100nm. The average particle size of the selected low-melting polyethylene (PE) particles is 500nm, and the ratio of the average pore size of the porous matrix to the average particle size of the low-melting polyethylene (PE) particles is 1:2.5, that is, the average pore size of the fiber porous matrix is ​​200nm, the ratio of the fiber porous matrix material to the polymer particle content is 95:5, and the isolation layer porosity is 75%. The cross-sectional porosity β of the isolation layer is 53%, the surface open porosity α is 88%, and the ratio of the cross-sectional porosity / surface open porosity β / α is 60%. Then, the above steps are repeated on the other surface of the positive electrode sheet, and then vacuum drying is performed at 40° C. to remove dispersants and solvents such as DMF, thereby obtaining a positive electrode sheet with a double-sided isolation layer coated thereon.

[0125] Example 2

[0126] The above method is the same as Example 1 except that the ratio of the fiber porous matrix material to the polymer particles is adjusted to 80:20 as shown in Table 1, the cross-sectional porosity β of the isolation layer is 56%, the surface porosity α is 80%, and the ratio of the cross-sectional porosity / surface porosity β / α is 70%.

[0127] Example 3

[0128] The above method is the same as Example 1 except that the ratio of the fiber porous matrix material to the polymer particles is adjusted to 65:35 as shown in Table 1, the cross-sectional porosity β of the isolation layer is 60%, the surface porosity α is 75%, and the ratio of the cross-sectional porosity / surface porosity β / α is 80%.

[0129] Example 4

[0130] The above method is the same as Example 1 except that the ratio of the fiber porous matrix material to the polymer particles is adjusted to 35:65 as shown in Table 1, the cross-sectional porosity β of the isolation layer is 50%, the surface porosity α is 65%, and the ratio of the cross-sectional porosity / surface porosity β / α is 77%.

[0131] Example 5

[0132] The above method is the same as Example 1 except that the ratio of the fiber porous matrix material to the polymer particles is adjusted to 5:95 as shown in Table 1, the cross-sectional porosity β of the isolation layer is 35%, the surface porosity α is 40%, and the ratio of the cross-sectional porosity / surface porosity β / α is 88%.

[0133] Example 6

[0134] Except that the fiber porous matrix material is PI, the rest is the same as Example 3.

[0135] Example 7

[0136] Except that the fiber porous matrix material is adjusted to PAN, the rest is the same as Example 3.

[0137] Example 8

[0138] Except that the polymer particle material is adjusted to ABS, the rest is the same as Example 3.

[0139] Example 9

[0140] Except that the polymer particle material is adjusted to PVB, the rest is the same as Example 3.

[0141] Example 10

[0142] The above steps are the same as those in Example 3 except that the average particle size of the polymer particles is adjusted to 200 nm as shown in Table 1, thereby adjusting the ratio of the pore size of the fiber porous matrix to the average particle size of the polymer particles to 1:1, the cross-sectional porosity β of the isolation layer to 55%, the surface porosity α to 70%, and the ratio of cross-sectional porosity / surface porosity β / α to 78%.

[0143] Embodiment 11

[0144] The above steps are the same as those in Example 3 except that the average particle size of the polymer particles is adjusted to 1000 nm as shown in Table 1, thereby adjusting the ratio of the pore size of the fiber porous matrix to the average particle size of the polymer particles to 1:5, the cross-sectional porosity β of the isolation layer to 60%, the surface porosity α to 80%, and the ratio of cross-sectional porosity / surface porosity β / α to 75%.

[0145] Example 12

[0146] The above steps are the same as those in Example 3 except that the average particle size of the polymer particles is adjusted to 3000 nm as shown in Table 1, thereby adjusting the ratio of the pore size of the fiber porous matrix to the average particle size of the polymer particles to 1:15, the cross-sectional porosity β of the isolation layer to 65%, the surface porosity α to 85%, and the ratio of cross-sectional porosity / surface porosity β / α to 75%.

[0147] Embodiment 13

[0148] The above steps are the same as those in Example 3 except that the pore size of the porous fiber matrix is ​​adjusted to 40 nm, the fiber diameter is adjusted to 10 nm, the average particle size of the polymer particles is adjusted to 10,000 nm, the cross-sectional porosity β of the isolation layer is 60%, the surface porosity α is 75%, and the ratio of cross-sectional porosity / surface porosity β / α is 80% as shown in Table 1.

[0149] Embodiment 14

[0150] The above method is the same as Example 3 except that the pore size of the fiber porous matrix is ​​adjusted to 1000nm, the fiber diameter is adjusted to 400nm, the polymer particle size is adjusted to 5000nm, the cross-sectional porosity β of the isolation layer is 65%, the surface porosity α is 80%, and the ratio of cross-sectional porosity / surface porosity β / α is 81% as shown in Table 1.

[0151] Embodiment 15

[0152] The above method is the same as Example 3 except that the pore size of the fiber porous matrix is ​​adjusted to 40nm, the fiber diameter is adjusted to 20nm, the average particle size of the polymer particles is adjusted to 40nm, the cross-sectional porosity β of the isolation layer is 50%, the surface porosity α is 70%, and the ratio of cross-sectional porosity / surface porosity β / α is 71% according to Table 1.

[0153] Example 16

[0154] Except that the thickness of the isolation layer is adjusted to 5 μm according to Table 1, and the cross-sectional porosity β of the isolation layer is 65%, the surface porosity α is 80%, and the ratio of cross-sectional porosity / surface porosity β / α is 81%, the rest is the same as Example 11.

[0155] Embodiment 17

[0156] Except for adjusting the porosity of the isolation layer to 30%, the cross-sectional porosity β of the isolation layer to 25%, the surface porosity α to 35%, and the cross-sectional porosity / surface porosity ratio β / α to 71% according to Table 1, the rest is the same as Example 11.

[0157] Embodiment 18

[0158] Except for adjusting the isolation layer porosity to 30% according to Table 1, the isolation layer cross-sectional porosity β to 80%, the surface opening porosity α to 85%, and the cross-sectional porosity / surface opening porosity ratio β / α to 94%, the rest is the same as Example 11.

[0159] Embodiment 19

[0160] The method is the same as Example 11 except that the low melting point polymer particle material is adjusted to EVA with a melting point of 70°C, and the cross-sectional porosity β of the isolation layer is 65%, the surface porosity α is 80%, and the ratio of cross-sectional porosity / surface porosity β / α is 81%.

[0161] Embodiment 20

[0162] Except that the low-melting-point polymer particle material is adjusted to PP with a melting point of 150°C, and the cross-sectional porosity β of the isolation layer is 65%, the surface porosity α is 80%, and the ratio of cross-sectional porosity / surface porosity β / α is 81%, the rest is the same as Example 11.

[0163] Embodiment 21

[0164] Polyvinylidene fluoride (PVDF) was dispersed in a dimethylformamide (DMF) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. Low melting point polyethylene (PE) particles were dispersed in an N-methylpyrrolidone (NMP) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%.

[0165] On one surface of the positive electrode plate of Preparation Example 2, solution A is used as a raw material to prepare a PVDF fiber porous matrix by an electrospinning method. While spinning, suspension B is used as a raw material to spray low-melting polyethylene (PE) particles on the same surface of the positive electrode plate by an electrospraying method to form an integrated isolation layer of a fiber porous matrix + a low-melting polymer with a thickness of 10 μm. The low-melting polymer particles are distributed in the fiber porous matrix in a filling manner. Among them, the average fiber diameter is 100nm. The average particle size of the selected low-melting polyethylene (PE) particles is 10000nm, and the ratio of the average pore size of the fiber porous matrix to the average particle size of the low-melting polyethylene (PE) particles is 1:50, that is, the average pore size of the fiber porous matrix is ​​200nm, the ratio of the fiber porous matrix material to the polymer particle content is 95:5, and the porosity of the isolation layer is 90%. The number of the polymer particles per unit area of ​​the porous matrix is ​​1×10 8 / m 2The cross-sectional porosity β of the isolation layer is 75%, the surface porosity α is 90%, and the cross-sectional porosity / surface porosity ratio β / α is 83%. Then, the above steps are repeated on the other surface of the positive electrode sheet, and then vacuum drying is performed at 40°C to remove the dispersant and solvent such as DMF, thereby obtaining a positive electrode sheet with a double-sided isolation layer.

[0166] Embodiment 22

[0167] Polyvinylidene fluoride (PVDF) was dispersed in a dimethylformamide (DMF) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. Low melting point polyethylene (PE) particles were dispersed in an N-methylpyrrolidone (NMP) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%.

[0168] On one surface of the positive electrode plate of Preparation Example 2, solution A is used as a raw material to prepare a PVDF fiber porous matrix by an electrospinning method. While spinning, suspension B is used as a raw material to spray low-melting polyethylene (PE) particles by an electrospraying method to form an integrated isolation layer of a fiber porous matrix + a low-melting polymer with a thickness of 20 μm. The low-melting polymer particles are distributed in the fiber porous matrix in a filling manner. Among them, the average fiber diameter is 10 nm. The average particle size of the selected low-melting polyethylene (PE) particles is 40 nm, and the ratio of the average pore size of the fiber matrix to the average particle size of the low-melting polyethylene (PE) particles is 1:1, that is, the average pore size of the fiber porous matrix is ​​40 nm, and the ratio of the fiber porous matrix material to the polymer particle content is 5:95, and the isolation layer porosity is 30%. The number of the polymer particles per unit area of ​​the porous matrix is ​​4×10 17 / m 2 The cross-sectional porosity β of the isolation layer is 25%, the surface porosity α is 45%, and the cross-sectional porosity / surface porosity ratio β / α is 56%. Then, the above steps are repeated on the other surface of the positive electrode sheet, and then vacuum drying is performed at 40°C to remove the dispersant and solvent such as DMF, thereby obtaining a positive electrode sheet with a double-sided isolation layer.

[0169] Embodiment 23

[0170] Polyvinylidene fluoride (PVDF) was dispersed in a dimethylformamide (DMF) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. Low melting point polyethylene (PE) particles were dispersed in an N-methylpyrrolidone (NMP) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%.

[0171] On one surface of the positive electrode plate of Preparation Example 2, solution A is used as a raw material to prepare a PVDF fiber porous matrix by an electrospinning method. While spinning, suspension B is used as a raw material to spray low-melting polyethylene (PE) particles by an electrospraying method to form an integrated isolation layer of a fiber porous matrix + a low-melting polymer with a thickness of 1 μm. The low-melting polymer particles are distributed in the fiber porous matrix in a filling manner. Among them, the average fiber diameter is 100nm. The average particle size of the selected low-melting polyethylene (PE) particles is 1000nm, and the ratio of the average pore size of the fiber matrix to the average particle size of the low-melting polyethylene (PE) particles is 1:5, that is, the average pore size of the fiber porous matrix is ​​200nm, the ratio of the fiber porous matrix material to the polymer particle content is 95:5, and the porosity of the isolation layer is 90%. The weight of the polymer particles in the porous matrix per unit area is 0.004g / m 2 The cross-sectional porosity β of the isolation layer is 70%, the surface porosity α is 85%, and the cross-sectional porosity / surface porosity ratio β / α is 82%. Then, the above steps are repeated on the other surface of the positive electrode sheet, and then vacuum drying is performed at 40°C to remove the dispersant and solvent such as DMF, thereby obtaining a positive electrode sheet with a double-sided isolation layer.

[0172] Embodiment 24

[0173] Polyvinylidene fluoride (PVDF) was dispersed in a dimethylformamide (DMF) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. Low melting point polyethylene (PE) particles were dispersed in an N-methylpyrrolidone (NMP) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%.

[0174] On one surface of the positive electrode plate of Preparation Example 2, solution A is used as a raw material to prepare a PVDF fiber porous matrix by an electrospinning method. While spinning, suspension B is used as a raw material to spray low-melting polyethylene (PE) particles by an electrospraying method to form an integrated isolation layer of a fiber porous matrix + a low-melting polymer with a thickness of 20 μm. The low-melting polymer particles are distributed in the fiber porous matrix in a filling manner. Among them, the average fiber diameter is 10nm. The average particle size of the selected low-melting polyethylene (PE) particles is 40nm, and the ratio of the average pore size of the fiber matrix to the average particle size of the low-melting polyethylene (PE) particles is 1:1, that is, the average pore size of the fiber porous matrix is ​​40nm, the ratio of the fiber porous matrix material to the polymer particle content is 5:95, and the porosity of the isolation layer is 30%. The weight of the polymer particles in the porous matrix per unit area is 20g / m 2The cross-sectional porosity β of the isolation layer is 25%, the surface porosity α is 45%, and the cross-sectional porosity / surface porosity ratio β / α is 56%. Then, the above steps are repeated on the other surface of the positive electrode sheet, and then vacuum drying is performed at 40°C to remove the dispersant and solvent such as DMF, thereby obtaining a positive electrode sheet with a double-sided isolation layer.

[0175] Embodiment 25

[0176] Polyvinylidene fluoride (PVDF) was dispersed in a dimethylformamide (DMF) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. Low melting point polyethylene (PE) particles were dispersed in an N-methylpyrrolidone (NMP) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%.

[0177] On one surface of the positive electrode plate of Preparation Example 2, solution A is used as a raw material to prepare a PVDF fiber porous matrix by an electrospinning method. While spinning, suspension B is used as a raw material to spray low-melting polyethylene (PE) particles by an electrospraying method to form an integrated isolation layer of a fiber porous matrix + a low-melting polymer with a thickness of 20 μm, and the low-melting polymer particles are distributed in the fiber porous matrix in a filling manner. Among them, the average fiber diameter is 100nm. The average particle size of the selected low-melting polyethylene (PE) particles is 10000nm, and the ratio of the average pore size of the fiber matrix to the average particle size of the low-melting polyethylene (PE) particles is 1:1, that is, the average pore size of the fiber porous matrix is ​​10000nm, the ratio of the fiber porous matrix material to the polymer particle content is 65:35, and the porosity of the isolation layer is 75%. And the cross-sectional porosity β of the isolation layer is 60%, the surface open porosity α is 80%, and the ratio of the cross-sectional porosity / surface open porosity β / α is 75%. The height of the polymer particles above the surface of the fiber porous matrix is ​​5000 nm. Then, the above steps are repeated on the other surface of the positive electrode sheet, and then vacuum drying is performed at 40°C to remove the dispersant and solvent such as DMF, thereby obtaining a positive electrode sheet with a double-sided isolation layer coated thereon.

[0178] Embodiment 26

[0179] Polyvinylidene fluoride (PVDF) was dispersed in a dimethylformamide (DMF) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. Low melting point polyethylene (PE) particles were dispersed in an N-methylpyrrolidone (NMP) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%.

[0180] On one surface of the positive electrode plate of Preparation Example 2, solution A is used as a raw material to prepare a PVDF fiber porous matrix by an electrospinning method. While spinning, suspension B is used as a raw material to spray low-melting polyethylene (PE) particles by an electrospraying method to form an integrated isolation layer of a fiber porous matrix + a low-melting polymer with a thickness of 20 μm, and the low-melting polymer particles are distributed in the fiber porous matrix in a filling manner. Among them, the average fiber diameter is 1000nm. The average particle size of the selected low-melting polyethylene (PE) particles is 10000nm, the ratio of the average pore size of the fiber matrix to the average particle size of the low-melting polyethylene (PE) particles is 1:5, that is, the average pore size of the fiber porous matrix is ​​2000nm, the ratio of the fiber porous matrix material to the polymer particle content is 5:95, and the porosity of the isolation layer is 30%. The cross-sectional porosity β of the isolation layer is 25%, the surface open porosity α is 35%, and the ratio of the cross-sectional porosity / surface open porosity β / α is 71%. The surface area of ​​the isolation layer occupied by polymer particles is 60%. Then, the above steps are repeated on the other surface of the positive electrode sheet, and then vacuum drying is performed at 40°C to remove dispersants and solvents such as DMF, thereby obtaining a positive electrode sheet with isolation layers coated on both sides.

[0181] Embodiment 27

[0182] Polyvinylidene fluoride (PVDF) was dispersed in a dimethylformamide (DMF) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. Low melting point polyethylene (PE) particles were dispersed in an N-methylpyrrolidone (NMP) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%.

[0183] On one surface of the positive electrode plate of Preparation Example 2, solution A is used as a raw material to prepare a PVDF fiber porous matrix by an electrospinning method. While spinning, suspension B is used as a raw material to spray low-melting polyethylene (PE) particles by an electrospraying method to form an integrated isolation layer of a fiber porous matrix + a low-melting polymer with a thickness of 10 μm, and the low-melting polymer particles are distributed in the fiber porous matrix in a filling manner. Among them, the average fiber diameter is 100nm. The average particle size of the selected low-melting polyethylene (PE) particles is 1000nm, and the ratio of the average pore size of the fiber matrix to the average particle size of the low-melting polyethylene (PE) particles is 1:5, that is, the average pore size of the porous matrix is ​​200nm. The ratio of the fiber porous matrix material to the polymer particle content is 65:35, the porosity of the isolation layer is 50%, the cross-sectional porosity β of the isolation layer is 45%, the surface open porosity α is 60%, and the ratio of the cross-sectional porosity / surface open porosity β / α is 75%. 。 Then, the above steps are repeated on the other surface of the positive electrode sheet, and then vacuum drying is performed at 40° C. to remove dispersants and solvents such as DMF, thereby obtaining a positive electrode sheet with a double-sided isolation layer coated thereon.

[0184] Embodiment 28

[0185] Polyvinylidene fluoride (PVDF) was dispersed in a dimethylformamide (DMF) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. Low melting point polyethylene (PE) particles were dispersed in an N-methylpyrrolidone (NMP) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%.

[0186] On one surface of the positive electrode plate of Preparation Example 2, solution A is used as a raw material to prepare a PVDF fiber porous matrix by an electrospinning method. While spinning, suspension B is used as a raw material to spray low-melting polyethylene (PE) particles by an electrospraying method to form an integrated isolation layer of a fiber porous matrix + a low-melting polymer with a thickness of 20 μm, and the low-melting polymer particles are distributed in the fiber porous matrix in a filling manner. Among them, the average fiber diameter is 100nm. The average particle size of the selected low-melting polyethylene (PE) particles is 10000nm, and the ratio of the average pore size of the fiber matrix to the average particle size of the low-melting polyethylene (PE) particles is 1:2.5, that is, the average pore size of the porous matrix is ​​4000nm, and the ratio of the fiber porous matrix material to the polymer particle content is 95:5. The porosity of the isolation layer is 90%. The cross-sectional porosity β of the isolation layer is 85%, the surface open porosity α is 90%, and the ratio of the cross-sectional porosity / surface open porosity β / α is 94%. . Then, the above steps are repeated on the other surface of the positive electrode sheet, and then vacuum drying is performed at 40° C. to remove dispersants and solvents such as DMF, thereby obtaining a positive electrode sheet with a double-sided isolation layer coated thereon.

[0187] Embodiment 29

[0188] Polyvinylidene fluoride (PVDF) was dispersed in a dimethylformamide (DMF) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. Low melting point polyethylene (PE) particles were dispersed in an N-methylpyrrolidone (NMP) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%.

[0189] On one surface of the positive electrode plate of Preparation Example 2, solution A is used as a raw material to prepare a PVDF fiber porous matrix by an electrospinning method. While spinning, suspension B is used as a raw material to spray low-melting polyethylene (PE) particles by an electrospraying method to form an integrated isolation layer of a fiber porous matrix + a low-melting polymer with a thickness of 10 μm, and the low-melting polymer particles are distributed in the fiber porous matrix in a filling manner. Among them, the average fiber diameter is 100nm. The average particle size of the selected low-melting polyethylene (PE) particles is 1000nm, the ratio of the average pore size of the fiber matrix to the average particle size of the low-melting polyethylene (PE) particles is 1:2.5, that is, the average pore size of the porous matrix is ​​400nm, the ratio of the fiber porous matrix material to the polymer particle content is 65:35, and the porosity of the isolation layer is 75%. Among them, the cross-sectional porosity β of the isolation layer is 40%, the surface open porosity α is 80%, and the ratio of the cross-sectional porosity / surface open porosity β / α is 50%. Then, the above steps are repeated on the other surface of the positive electrode sheet, and then vacuum drying is performed at 40° C. to remove dispersants and solvents such as DMF, thereby obtaining a positive electrode sheet with a double-sided isolation layer coated thereon.

[0190] Embodiment 30

[0191] Polyvinylidene fluoride (PVDF) was dispersed in dimethylformamide (DMF) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. Low melting point polyethylene (PE) particles were dispersed in N-methylpyrrolidone (NMP) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%. Inorganic particles of aluminum oxide (Al2O3) and polyvinylidene fluoride (PVDF) were mixed at a weight ratio of 90:10, and N-methylpyrrolidone (NMP) was added as a solvent to prepare a slurry C with a solid content of 40%.

[0192] On one surface of the positive electrode sheet of Preparation Example 2, solution A was used as a raw material to prepare a PVDF fiber porous matrix by an electrospinning method. During the spinning process, suspension B and slurry C were used as raw materials to spray low-melting polyethylene (PE) particles and inorganic particles of aluminum oxide (Al2O3) by an electrospraying method to form an integrated isolation layer of PVDF fiber porous matrix + low-melting polymer + inorganic particles with a thickness of 10 μm, and the low-melting polymer particles and inorganic particles were embedded in the pores of the fiber porous matrix. The average fiber diameter was 100 nm. The average particle size of the selected low-melting polyethylene (PE) particles is 1000nm, the ratio of the average pore size of the fiber matrix to the average particle size of the low-melting polyethylene (PE) particles is 1:5, that is, the average pore size of the porous matrix is ​​200nm, the average particle size of the selected inorganic ceramic (Al2O3) particles is 400nm, the weight ratio of the fiber porous matrix material to the polymer particles and the inorganic particles is 60:30:10, and the porosity of the isolation layer is 70%. The cross-sectional porosity β of the isolation layer is 55%, the surface open porosity α is 70%, and the ratio of the cross-sectional porosity / surface open porosity β / α is 79%. Then, repeat the above steps on the other surface of the positive electrode plate, and then vacuum dry at 40°C to remove the dispersant and solvent such as DMF, and then obtain a positive electrode plate with a double-sided isolation layer coating.

[0193] Embodiment 31

[0194] Preparation of positive electrode

[0195] Conductive carbon black (SuperP) and styrene-butadiene rubber (SBR) were mixed at a weight ratio of 97:3, and deionized water (H2O) was added as a solvent to prepare a slurry with a solid content of 0.85, and stirred evenly. The slurry was evenly coated on the positive electrode current collector aluminum foil and dried at 110°C to obtain a positive electrode bottom coating.

[0196] The positive electrode active material lithium cobalt oxide (LiCoO2), conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97.5:1.0:1.5, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 0.75, and stirred evenly. The slurry is evenly coated on the positive electrode current collector aluminum foil coated with the primer, and dried at 90°C to obtain a positive electrode sheet. After coating, the sheet is cut into a specification of 38mm×58mm for standby use.

[0197] Polyvinylidene fluoride (PVDF) was dispersed in a dimethylformamide (DMF) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. Low melting point polyethylene (PE) particles were dispersed in an N-methylpyrrolidone (NMP) / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%.

[0198] On one surface of the positive electrode sheet prepared in this embodiment, solution A is used as a raw material to prepare a PVDF fiber porous matrix by an electrospinning method. While spinning, suspension B is used as a raw material to spray low-melting polyethylene (PE) particles by an electrospraying method to form an integrated isolation layer of a fiber porous matrix + a low-melting polymer with a thickness of 10 μm, and the low-melting polymer particles are distributed in the fiber porous matrix in a filling manner. Among them, the average fiber diameter is 100nm. The average particle size of the selected low-melting polyethylene (PE) particles is 1000nm, the ratio of the average pore size of the fiber matrix to the average particle size of the low-melting polyethylene (PE) particles is 1:5, that is, the average pore size of the porous matrix is ​​200nm, the ratio of the fiber porous matrix material to the polymer particle content is 65:35, the cross-sectional porosity β of the isolation layer is 65%, the surface open porosity α is 80%, and the ratio of the cross-sectional porosity / surface open porosity β / α is 81%. 。 Then, the above steps are repeated on the other surface of the positive electrode sheet, and then vacuum drying is performed at 40° C. to remove dispersants and solvents such as DMF, thereby obtaining a positive electrode sheet with a double-sided isolation layer coated thereon.

[0199] Preparation of lithium-ion batteries

[0200] The negative electrode sheet prepared in the above Preparation Example 1 and the positive electrode sheet with a separation layer prepared in each embodiment are stacked opposite to each other. Figure 2 After the four corners of the entire laminate structure are fixed with tape, it is placed in an aluminum-plastic film, sealed on the top and sides, injected with the electrolyte in Preparation Example 3, and then packaged to obtain a lithium-ion laminated battery.

[0201] The data and test results of each embodiment are shown in Table 1, Table 2 and Table 3.

[0202] Comparative Example 1

[0203] A polyethylene (PE) with a thickness of 15 μm was selected as a separator and placed between the negative electrode sheet and the positive electrode sheet prepared in the above-mentioned Preparation Examples 1 and 2 as a separator. The negative electrode sheet, the positive electrode sheet and the separator were stacked opposite to each other. After the four corners of the entire laminate structure were fixed with tape, it was placed in an aluminum-plastic film, top and side sealed, the electrolyte in Preparation Example 3 was injected, and packaging was performed to obtain a lithium-ion laminated battery.

[0204] Comparative Example 2

[0205] PVDF was dispersed in a dimethylformamide DMF / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. On one surface of the positive electrode sheet prepared in Preparation Example 2, a layer of PVDF non-woven fiber layer with a thickness of 10 μm was prepared by electrospinning using solution A as a raw material, the fiber layer had a diameter of 100 nm, an average pore size of 200 nm, and a porosity of 75%. Then, the above steps were repeated on the other surface of the positive electrode sheet, and the dispersant of the polymer coating was dried at 90°C to obtain a positive electrode sheet with PVDF non-woven fiber layers on both sides.

[0206] The positive electrode sheet is placed opposite to the negative electrode sheet prepared in Preparation Example 1 and stacked. Figure 2 After the four corners of the entire laminate structure are fixed with tape, it is placed in an aluminum-plastic film, top and side sealed, the electrolyte in Preparation Example 3 is injected, and packaging is performed to obtain a lithium-ion laminated battery.

[0207] Comparative Example 3

[0208] A polyethylene (PE) with a thickness of 15 μm was selected as the isolation membrane. Low-melting-point polyethylene (PE) particles were dispersed in N-methylpyrrolidone NMP / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%. A 5 μm low-melting-point polyethylene (PE) particle coating was prepared on the surface of the polyethylene isolation membrane by electrospraying, wherein the average particle size of the particles was 500 nm. The total thickness of the isolation layer was 20 μm, and the overall porosity of the isolation layer was 30%.

[0209] The above-prepared integrated separator containing the low melting point polymer particle coating is placed between the negative electrode sheet and the positive electrode sheet prepared in the above-mentioned preparation examples 1 and 2. The negative electrode sheet, the positive electrode sheet and the separator are stacked opposite to each other. After the four corners of the entire stacked structure are fixed with tape, it is placed in an aluminum-plastic film, and after top and side sealing, the electrolyte in the preparation example 3 is injected, and packaging, a lithium-ion stacked battery is obtained.

[0210] Comparative Example 4

[0211] PVDF was dispersed in a dimethylformamide DMF / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a solution A with a mass fraction of 25%. At the same time, low melting point polyethylene (PE) particles were dispersed in an N-methylpyrrolidone NMP / acetone (7:3) solvent and stirred evenly until the slurry viscosity was stable to obtain a suspension B with a mass fraction of 40%.

[0212] On one surface of the positive electrode sheet prepared in Preparation Example 2, a PVDF non-woven fiber layer with a thickness of 10 μm was prepared by electrospinning using solution A as a raw material, the average fiber diameter was 100 nm, and the average pore size of the fiber porous matrix was 200 nm. After spinning, low-melting polyethylene (PE) particles were prepared on the surface of the fiber porous matrix using suspension B as a raw material by electrospraying, the average particle size of the low-melting polyethylene (PE) particles was 500 nm, the ratio of the average pore size of the fiber porous matrix to the average particle size of the low-melting polyethylene (PE) particles was 1:25, and the overall porosity of the isolation layer was 75%. Then, the above steps were repeated on the other surface of the positive electrode sheet, and the dispersant such as DMF was removed by vacuum drying at 40°C to obtain a positive electrode sheet with an isolation layer on both sides.

[0213] The positive electrode sheet and the negative electrode sheet prepared in Preparation Example 1 are stacked opposite each other. Figure 2 After the four corners of the entire laminate structure are fixed with tape, it is placed in an aluminum-plastic film, top and side sealed, the electrolyte of Preparation Example 3 is injected, and packaging is performed to obtain a lithium-ion laminated battery.

[0214] The data and test results of Comparative Examples 1-4 are shown in Table 1, Table 2 and Table 3.

[0215]

[0216]

[0217]

[0218] Table 2

[0219]

[0220]

[0221] Table 3

[0222]

[0223]

[0224] It can be seen from Tables 1, 2 and 3 that, compared with ordinary separators, the integrated isolation layer of low-melting-point polymer particles filled with nanofiber porous matrix can reduce the thickness of the isolation layer to increase the energy density, increase the porosity of the isolation layer to improve the liquid retention capacity, accelerate the reaction kinetics to enhance the electrical performance, enhance the adhesion between the isolation layer and the pole piece to improve the mechanical abuse performance of the lithium-ion battery such as anti-drop, reduce the closed-cell temperature of the isolation layer, and improve its resistance to thermal shrinkage in high temperature environments, thereby improving the safety and stability of lithium-ion batteries.

[0225] Compared with the heat-resistant spinning isolation layer, the isolation layer of the present application has low-melting polymer particles distributed in the nanofiber porous matrix, so that the isolation layer of the present application has a low-temperature thermal pore-closing function, and can cut off the current under thermal runaway to improve the safety performance of lithium-ion batteries. In addition, low-melting polymer particles can be filled in the "macroporous" of the fiber porous matrix, reducing the macropores in the pure heat-resistant spinning isolation layer, thereby further improving the self-discharge problem of lithium-ion batteries and reducing the K value. At the same time, due to the improvement of the mechanical strength of the isolation layer, the internal short circuit problem of the positive and negative active material particles in the lithium-ion battery piercing the isolation layer is reduced, which is also conducive to improving the cycle performance of lithium-ion batteries.

[0226] Compared with the two-layer structure of ordinary diaphragm + low melting point polymer particle isolation layer, the integrated structure design halves the thickness of the isolation layer, thereby greatly improving the volume energy density of lithium-ion batteries. At the same time, due to the high melting point and good high temperature stability of the fiber porous matrix, the risk of high temperature shrinkage or even rupture of the isolation layer can be reduced, making the lithium-ion battery have excellent safety performance. In addition, the integrated isolation layer has a higher porosity, which accelerates ion transmission, enhances reaction kinetics, and improves the electrical performance of lithium-ion batteries.

[0227] Compared with the two-layer structure of heat-resistant spinning layer + low-melting point polymer particles, the integrated structural design can effectively reduce the thickness of the isolation layer, making the lithium-ion battery have a higher volume energy density. At the same time, the low-melting point polymer is filled in the fiber porous matrix, and the melting and closing of the pores respond faster when thermal runaway occurs. In addition, the low-melting point polymer fills the "large pores" in the fiber porous matrix, optimizes the pore size distribution, improves the self-discharge problem of lithium-ion batteries, reduces the K value, and improves the mechanical strength of the fiber porous matrix, enhancing the ability to resist puncture of positive and negative electrode particles.

[0228] The above description is only a preferred embodiment of the present application and is not intended to limit the protection scope of the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application are included in the protection scope of the present application.

Claims

1. An electrochemical device comprising an electrode plate and a separation layer on at least one surface of the electrode plate, wherein the separation layer comprises a porous matrix of nanofibers and polymer particles distributed in the porous matrix, wherein the melting temperature of the polymer particles is 70° C. to 150° C., and the number of the polymer particles in the separation layer is 1×10 8 / m 2 Up to 1×10 18 / m 2 The average particle size of the polymer particles is 40nm to 10μm, some polymer particles extend from the surface of the porous matrix to a height of 5nm-20nm, the ratio β / α between the cross-sectional void ratio β and the surface porosity α of the isolation layer is 71%-81%, the surface porosity α is 70%-90%, and the thickness of the isolation layer is 6μm to 20μm.

2. The electrochemical device according to claim 1, wherein: The diameter of the nanofiber is 10 nm to 5 μm, and the pore size of the fiber porous matrix is ​​40 nm to 10 μm.

3. The electrochemical device according to claim 1, wherein The surface area of ​​the porous matrix occupied by the polymer particles is 0.1% to 60% of the total surface area of ​​the porous matrix.

4. The electrochemical device according to claim 1, wherein the polymer of the polymer particles comprises at least one of polystyrene, polyethylene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, acrylonitrile-butadiene-styrene, polylactic acid, polyvinyl chloride, polyvinyl butyral, or polyacrylate.

5. The electrochemical device according to claim 1, wherein The nanofibers contain a polymer, and the polymer includes at least one of polyvinylidene fluoride, polyimide, polyamide, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polyphenylene ether, polypropylene carbonate, polymethyl methacrylate, polyethylene terephthalate, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-co-chlorotrifluoroethylene) and their derivatives.

6. The electrochemical device according to claim 5, wherein: The polymer includes at least one of polyvinylidene fluoride, polyimide, polyamide, polyacrylonitrile, polyethylene glycol, polyethylene oxide, polyphenylene ether, polypropylene carbonate, polymethyl methacrylate, polyethylene terephthalate and derivatives thereof.

7. The electrochemical device according to claim 1, wherein: The polymer of the nanofibers also contains inorganic particles, and the inorganic particles include at least one of HfO2, SrTiO3, SiO2, Al2O3, MgO, CaO, NiO, BaO, ZnO, TiO2, ZrO2, SnO2, CeO2, boehmite, magnesium hydroxide or aluminum hydroxide. The electrochemical device according to claim 1 , wherein the cross-sectional void ratio β is 30% to 85%.

9. An electronic device comprising the electrochemical device according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Organic / inorganic composite porous isolating membrane

    CN101707242A

  • Organic-inorganic composite membrane as well as preparation and application thereof

    CN103311486A

  • Lithium battery separator with shutdown function

    CN103329309A

  • Composite electrode plate of lithium ion battery, preparation method of composite electrode plate and lithium ion battery

    CN104124414A

  • Isolating membrane of electrochemical device and preparation method and application of isolating membrane

    CN106129313A